2008
DOI: 10.1002/jbm.a.31929
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of metal and tissue adhesion on surface‐modified parylene C

Abstract: A general method for chemical surface functionalization of parylene C [PC, (para-CH2-C6H3Cl-CH2-)n] films is reported. Friedel-Crafts acylation is used to activate the surface of the PC film, and the resulting carbonyl groups are then used to form a range of different organic functional groups to the surface of the parylene film, including alcohol, imine, thiol, phthalimide, amine, and maleimide. The presence of these functional groups on the parylene surface was confirmed by Fourier transform infrared spectro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 37 publications
0
28
0
Order By: Relevance
“…The solution was sonochemically irradiated with an immersed Ti-horn (20 kHz, 750 W at 70% efficiency). The Ti(i-OPr) 4 in concentrations of 10-20 g/L was added drop-wise to the working solution under sonication, and the process continued for 1 h. After the reaction, the coated glass was washed with water and ethanol and allowed to dry in air at room temperature. For the stabilization of TiO 2 in the dispersed state, PVP (MW = 89,000-98,000) was added to the reaction slurry before sonication at a concentration range of 3-12 g/L.…”
Section: Deposition Of Tio 2 On Parylene Glassmentioning
confidence: 99%
See 2 more Smart Citations
“…The solution was sonochemically irradiated with an immersed Ti-horn (20 kHz, 750 W at 70% efficiency). The Ti(i-OPr) 4 in concentrations of 10-20 g/L was added drop-wise to the working solution under sonication, and the process continued for 1 h. After the reaction, the coated glass was washed with water and ethanol and allowed to dry in air at room temperature. For the stabilization of TiO 2 in the dispersed state, PVP (MW = 89,000-98,000) was added to the reaction slurry before sonication at a concentration range of 3-12 g/L.…”
Section: Deposition Of Tio 2 On Parylene Glassmentioning
confidence: 99%
“…Ti(i-OPr) 4 was used as a precursor for the synthesis of TiO 2 . The TiO 2 nanoparticles (NPs) were deposited on the Parylene-glass slides by the ultrasound-assisted hydrolysis of Ti(i-OPr) 4 . The procedure was as follows.…”
Section: Deposition Of Tio 2 On Parylene Glassmentioning
confidence: 99%
See 1 more Smart Citation
“…The most common parylene materials are parylene N, parylene D, and parylene C [poly(chloro-p-xylylene)] (PC). PC is hydrophobic and is conformably deposited and chemically inert toward most common organic and biological fluids and water till up to 150°C (10). It has a high resistance and elasticity, low dielectric constant, and the highest biocompatibility certification with United States Pharmacopeial Class VI (11,12).…”
Section: Introductionmentioning
confidence: 99%
“…These modification methods have been suggested to have their roles in medical applications, such as anti-biofouling, temperature responsive biosensors, controlled drug release, thermal responsive chromatography, and reversible cell adhesion/detachment. [26][27][28][29][30][31][32][33][34][35] Among this applications, homo pNIPAM grafted substrates has been intensely applied for mammalian cell adhesion/detachment study. 34,36,37 Below LCST, it has been found that the cells do not adhere to the pNIPAM-coated substrate.…”
Section: Introductionmentioning
confidence: 99%